2020
DOI: 10.1083/jcb.201905071
|View full text |Cite
|
Sign up to set email alerts
|

Caveolae and lipid sorting: Shaping the cellular response to stress

Abstract: Caveolae are an abundant and characteristic surface feature of many vertebrate cells. The uniform shape of caveolae is characterized by a bulb with consistent curvature connected to the plasma membrane (PM) by a neck region with opposing curvature. Caveolae act in mechanoprotection by flattening in response to increased membrane tension, and their disassembly influences the lipid organization of the PM. Here, we review evidence for caveolae as a specialized lipid domain and speculate on mechanisms that link ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 183 publications
(209 reference statements)
1
59
0
Order By: Relevance
“…Due to specific composition of rafts, also their local curvature may be different than in other membrane regions. Indeed, such formations also called caveolae were observed in experiments [59] indicating that curvature underlays a sorting mechanism connecting the shape and the composition of biological membranes. Recently, it was observed that endocytosis in diverse cell types was connected to formation of membrane domains [53].…”
Section: Curvature-sorting and Composition Of Evsmentioning
confidence: 94%
“…Due to specific composition of rafts, also their local curvature may be different than in other membrane regions. Indeed, such formations also called caveolae were observed in experiments [59] indicating that curvature underlays a sorting mechanism connecting the shape and the composition of biological membranes. Recently, it was observed that endocytosis in diverse cell types was connected to formation of membrane domains [53].…”
Section: Curvature-sorting and Composition Of Evsmentioning
confidence: 94%
“…The plasma membranes of endothelial, muscle, and fat cells are packed with caveolae, suggesting an important role in specialized functions including homeostasis and metabolism. Caveolae also comprise a specific lipid environment containing large amounts of cholesterol, sphingomyelin, and ceramides (Graf et al, 1999 ; Parton et al, 2020b ; Zhou et al, 2020 ). These lipids accumulate in caveolae, providing a reservoir for these molecules (Hubert et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…As CHIM-L behaves similarly to cholesterol in model membranes, we next tested whether this is also observed in the membrane system of live cells. We first concentrated on caveolae, which represent cholesterol-rich PM invaginations functioning for instance as mechanosensors and cellular signaling regulators 22 , 23 . Cholesterol is recruited to such raft-like areas by interaction with the prime protein constituent caveolin1 (Cav1) 23 and serves a structural role as removal of cholesterol causes disruption and flattening of caveolae 24 , 25 .…”
Section: Resultsmentioning
confidence: 99%